NURALI KABUL‘S ARTISTIC INTERPRETATION OF THE ANIMAL WORLD AND HUMAN RELATIONS - Qurbonova, Gulbahor (FILOLOGIYA UFQLARI JURNALI, 2024)
The world was created in such a way that human is glorified by their intelligence and consciousness, which distinguishes him from other animals. Fiction also praises the intellectual potential of human, as well as the positive and negative effects of nature on humanity. This is the main theme of the story "Abyssal Sky" by the talented artist Nurali Kabul. This article analyzes how the story reflects the sacrifices of human beings for their own benefit. As proof of the author’s opinion, the story is subjected to a comparative analysis with examples of literature from different nations.